ANALISIS CAMPUR KODE PADA FILM NGERI NGERI SEDAP DAN IMPLIKASINYA PADA PEMBELAJARAN BAHASA INDONESIA - nanifauzi; Wahyu Ningsih; Hesi Ikesia Br Ginting; Gresselly Margareta Simarmata (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study was to determine the words included in code mixing in the Ngeri-Ngeri Sedap film by Bene Dion. This film is set in Batak culture and uses the original Batak language because it was recorded in an area that is still heavily influenced by Batak culture, especially the area around Lake Toba. The research method used in this study is descriptive qualitative. The free listening method and data recording procedures using speech from the Ngeri-Ngeri Sedap film were used to collect data for this study. The results of this study found 16 words included in code mixing and there were 3 slogans from the Ngeri-ngeri sedap film. Code mixing in the Ngeri-Ngeri Sedap film became the source of research data. Recording and listening techniques were used to collect data. Learning slogans to improve language comprehension and proficiency is one way to learn Indonesian that has consequences.